Role of the Phagocyte in Host-Parasite Interactions XXIV. Aldehyde Generation by the Myeloperoxidase-H(2)O(2)-Chloride Antimicrobial System: a Possible In Vivo Mechanism of Action - Paul, B. B. (1970)
Myeloperoxidase (MPO), H(2)O(2), and chloride ions in the presence of bacteria form aldehydes and are bactericidal. The use of heat-inactivated MPO prevented both killing and aldehyde generation. Decarboxylation and deamination of carboxyl and amino group substrates arising from the bacterial surface may participate in the reaction which yields aldehydes. Bacterial contact was essential for killing. Decarboxylation and bactericidal activities were noted when physiological concentrations of chloride were used. When MPO was replaced with horseradish peroxidase (HPO) in the chloride medium, decarboxylation and bactericidal activities were no longer noted. In contrast, iodide functioned in the antimicrobial system with either MPO or HPO. The iodide concentrations required were at least sixfold greater than circulating blood iodide levels. Moreover, decarboxylation did not occur in the presence of iodide with either enzyme. Thus, both halides function in the MPO-H(2)O(2) system but by different mechanisms. It is likely that in vivo under most conditions chloride is the functional halide and that generation of aldehydes is the mechanism responsible for the antimicrobial activity of the MPO-H(2)O(2)-chloride system.